Spatial Spread of Invasive Foreign Plants Clidemia hirta (L.) D. Don in Bung Hatta Forest Park, Padang, West Sumatra - Rian Anggraini; Solfiyeni Solfiyeni (Jurnal Biologi Universitas Andalas, 2019)
Research on Spatial Spread of Invasive Foreign Plants Clidemia hirta in Bung Hatta Forest Park, Padang, West Sumatra, has been carried out from January to June 2018. The purpose of this study was to determine the spatial distribution pattern of invasive foreign plants Clidemia hirta and analyze the influence of distance from roads and influence light intensity on the distribution of the number of individuals Clidemia hirta in the Bung Hatta Forest Park. This study uses a belt transect method with a width of 2 meters along 250 meters. Along the transect, a plot of 2x2 meters was made with 125 plots. Observations made on Clidemia hirta is to calculate the number of individuals and measure the intensity of light in each plot. The results showed that the pattern of spread of  Clidemia hirta was grouped with the Morisita Index of 2.1. The distance from the road and the intensity of light does not affect the distribution of the number of individuals with R Square values of 0.022 and 0.007, respectively.